Utilising NGT to evaluate the suitability and usability of Parent-Implemented Social Communication Strategies in Autism (PICA) Model among Speech-Language Therapists (SLTs) - Ab Aziz, Analiza Anis; Mohamed Zain, Nor Azrita; Jusoh, Masnira; Zakaria, Rozanizam (Journal of Islamic, Social, Economics and Development, 2025)
Parent-implemented social communication interventions are increasingly recognised as effective for improving the social communicative development of children with Autism Spectrum Disorder (ASD). These approaches train parents to embed therapeutic strategies into daily routines, creating naturalistic learning opportunities. Speech-language therapists (SLTs) are critical in guiding parents, ensuring intervention fidelity, and monitoring outcomes. However, the usability and suitability of such interventions within clinical practice remain underexplored. This study evaluates the newly developed Parent-Implemented Social Communication Strategies in Autism (PICA) model among Malaysian SLTs, focusing on training objectives, social communication components, parents' communication knowledge, parent-child interaction skills, and generalisation strategies. The Nominal Group Technique (NGT) obtained consensus from 27 Malaysian SLTs. Findings revealed strong agreement (93.1%–99.5%) on the model's suitability and usability across all five components. Prioritised elements included interaction, communicative function, and fidelity support. Despite the overall endorsement, skill generalisation and cultural adaptation challenges were noted. The study empirically validates the PICA model as a practical framework for parent-led intervention in Malaysia. It further underscores the need for technology-driven enhancements, such as AI applications and culturally responsive training, to enhance access and effectiveness of early intervention programs. These advancements are essential for supporting parents and consequently contribute to social communication outcomes in children with ASD.